“Serbatoi celesti”. La foresta come dispositivo di riconfigurazione dello spazio urbano - Grigoletto, Lorena; Grigoletto, Lorena (Mechane, 2023)
This article aims to reflect on the relationship between the forest (foris) and the city by analysing the importance it assumes on a literary and philosophical level, particularly in relation to the question of language and dwelling. Understood as a true founding metaphor for European culture, it undergoes an introjection into urban space, first through the architectural metaphor of the “lucus” and later as an “architectural device” which, however, seems incapable of contrasting the encroachment of contemporary cities and megalopolis, their programmatic reduction of the unrepresentable and the progressive impoverishment of the imaginary. In this perspective, we can understand the forest in terms of a “device”, rather than architectural, of vision and habitability, starting from the perceptive-sensorial dimension that it allows as a space that can be walked through, and then of a device for reconfiguring urban space capable, perhaps, of operating a resemantization of the relationship between oikos and polis.